Pengaruh Penerapan Sistem manajemen Sumber Daya Perusahaan (ERP) dalam meningkatkan Kinerja Manajemen Rantai Pasok (SCM) suatu Organisasi/Perusahaan - Tjan, Charles; Kelvin, Kelvin; Lim, Nicholas; Vincent, Vincent; Welwen, Welwen (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The food business is one business that can be said to be very popular throughout the world, including in Indonesia itself. The business will continue to grow over time. UMKM Blackforest Cakeshop is one of the developing UMKM in the food sector. in a growing business, the UMKM Blackforest Cakeshop also implements a system called the ERP system. In the ERP system, they use an application called Olsera where the manager works closely with the UMKM manager Blackforest Cakeshop. The research method that we use is to use qualitative methods. Using qualitative methods, we research and seek information about UMKM Blackforest Cakeshop. The purpose of our research is to find out whether UMKM Blackforest Cakeshop can take advantage of existing technology to develop their business. Keywords: ERP, Olsera, techonolgy, Blackforest Cakeshop.